2022
DOI: 10.1097/gco.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal torsion: a review of diagnosis and management strategies

Abstract: Purpose of reviewAdnexal torsion remains a diagnostic challenge heavily reliant on high clinical suspicion, with patient presentation and imaging used as adjuncts to aid in its diagnosis. This review summarizes diagnostic and management techniques of adnexal torsion to assist providers when encountering this surgical emergency. Recent findingsCommon findings of adnexal torsion include abdominal pain, nausea, vomiting, and adnexal mass or ovarian enlargement. An elevated neutrophil to lymphocyte ratio may be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It has become clear that the appearance of the ovary during surgery does not correlate well with subsequent ovarian recovery and function ( 10 , 11 , 19 ). According to current guidelines, oophorectomy is unnecessary in cases of black discoloration of the ovary seen during surgery ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become clear that the appearance of the ovary during surgery does not correlate well with subsequent ovarian recovery and function ( 10 , 11 , 19 ). According to current guidelines, oophorectomy is unnecessary in cases of black discoloration of the ovary seen during surgery ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This surgical approach was found to cause subfertility or early-onset menopause (9). In recent years, there has been a shift to a fertility sparing treatment, following studies that demonstrated viability of the ovary after detorsion (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In all studies examining follicular development in the preservation of the ovary after detorsion in humans, it has been shown that the function of the ovary continues. 4 However, the follicle cohort may be adversely affected despite the ovary remaining viable after detorsion. The increase in ovarian tissue damage has been attributed to oxidative stress products of post-ischemia reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tissue should be preserved as much as possible, since in most studies, normal follicle development is seen after detorsion of even an ovary that appears to be bluish-black in color during surgery. 4 In patients with torsion who have completed their fertility, are older, or have a suspected malignant mass, the surgeon can decide on an oophorectomy more easily. However, there are reservations about performing cystectomy during detorsion in young women and on masses that are presumed to be benign.…”
mentioning
confidence: 99%
“…Swelling and blood flow obstruction result from this. Initial obstruction of the venous outflow is followed by interruption of the arterial inflow as a result of increased swelling, which results in ovarian necrosis, infarction, hemorrhage, and possibly peritonitis [ 19 ]. Because the sigmoid colon is located in the left pelvis, the right side has been seen more frequently than the left; this is thought to be a result of the increased space in the right pelvis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%